(untitled) (Journal of Educational Sciences, 2021)
The technological and methodological aspects of the formation of digital creative competencies of future teachers in the context of distance learning in the Republic of Kazakhstan are defined and the essence of the following concepts: «competence», «digital competence» , «digital and technological competence», «digital and methodological competence», «creativity», «digital pedagogical campus» are identified in this article. The essence of the components of competence is characterized in a new context in this article such as organizational ability; empathic ability; reflective ability. The content of digital-technological and digital-methodological competencies of future teachers in the framework of distance learning is also revealed in this article. If the digital-technological competence of a future teacher in the conditions of distance learning is determined by the formation of his skills and abilities to work with Internet resources, digital learning platforms, modern computer programs, multimedia devices, thеn the digital-methodological competence of the future teacher is characterized by his ability to create an electronic portfolio, an electronic media library and the organization of pedagogical coaching and pedagogical trainings. In order to increase the digital creative competencies of future teachers in the Republic of Kazakhstan, the content of 8 pedagogical online resources that are part of the digital pedagogical campus SMART-future teacher is disclosed in more detail: SMART-online pedagogical seminar; SMART-online pedagogical studio; SMART-pedagogical electronic online library; SMART – online methodological portfolio (electronic portfolio); SMART-online coaching; SMART-online coworking center; SMART is a virtual online laboratory and SMART digital content. The content is revealed and a new model of the formation of digital-creative competencies of future teachers in the context of distance learning is offer. Key words: competence, digital competence, digital and technological competence, digital and methodological competence, digital pedagogical campus.